2014
DOI: 10.1093/pubmed/fdu076
|View full text |Cite
|
Sign up to set email alerts
|

Five-year follow-up study of the association between periodontal disease and myocardial infarction among Japanese male workers: MY Health Up Study

Abstract: Periodontal disease may be a mild but independent risk factor for MI among Japanese male workers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
17
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 35 publications
3
17
0
Order By: Relevance
“…Our results are consistent with previous studies that have demonstrated independent associations of PD with individual CVD outcomes (e.g. myocardial infarction), 14, 15 and with studies that have used proxies for either PD and/or CVD outcomes. 37, 38 However, there appear to be no previous studies that have directly examined the PD-FGRS association.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our results are consistent with previous studies that have demonstrated independent associations of PD with individual CVD outcomes (e.g. myocardial infarction), 14, 15 and with studies that have used proxies for either PD and/or CVD outcomes. 37, 38 However, there appear to be no previous studies that have directly examined the PD-FGRS association.…”
Section: Discussionsupporting
confidence: 92%
“…12 PD is known to be independently associated with these CVD outcomes predicted by the FGRS. [13][14][15] The CVD risk factors used in computing the FGRS, including age, diabetes, smoking, total cholesterol, and HDL, are also independently associated with PD. [16][17][18] The associations of PD with both the Framingham outcomes and risk factors suggest that PD may be a reasonable determinant to inform CVD risk.…”
mentioning
confidence: 99%
“…It is also one of the few works that have assessed the relationship between the number of teeth and MI [11,17,22,26,27,30]. The authors demonstrated a strong positive association between the extent of periodontitis and MI, independent of classical CVD risk factors, including tobacco smoking.…”
Section: Discussionmentioning
confidence: 99%
“…Some of them demonstrated that periodontitis constitutes an independent MI risk factor [10][11][12][13][14][15][16][17], whereas other studies did not confirm these relationships [18][19][20]. Therefore, the aim of this study was to answer the question whether the periodontitis severity and extent is an independent and significant risk factor for acute MI in adult Poles under the age of 70 years.…”
mentioning
confidence: 89%
“…In the adult USA population, nearly half of individuals aged >30 years have some periodontitis, and almost 10% of the population has severe periodontitis (Eke et al, 2012, 2015, 2016a,b). There is growing evidence suggesting that periodontitis is associated with increased MI risk (Wożakowska-Kapłon et al, 2013; Kodovazenitis et al, 2014; Noguchi et al, 2015; Rydén et al, 2016). Periodontitis shares some common risk factors with MI, such as diabetes and smoking (Kjellström et al, 2016).…”
Section: Introductionmentioning
confidence: 99%